2008
DOI: 10.1002/dc.20944
|View full text |Cite
|
Sign up to set email alerts
|

BAL in the diagnosis of smoking‐related interstitial lung diseases: Review of literature and analysis of our experience

Abstract: The group of interstitial lung diseases (ILDs) is formed by respiratory tract disorders, whose aetiology is unknown in the majority of cases, the clinical course differs and the prognosis is generally serious. Some of the ILDs have a potential relation to tobacco smoking and are known as smoking-related ILDs (sr-ILD). Bronchoalveolar lavage fluid (BALF) examination is one of the initial procedures in the diagnosis of ILD. Despite the fact that histological confirmation is the gold standard in ILD diagnosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 38 publications
1
10
0
2
Order By: Relevance
“…In addition, it should be pointed that reporting cell proportions is, in fact, limited to showing relativity, and this may be misleading. A good example can be seen in our previous studies on sr-ILD [20]. The differential cell count in the BALF of patients with desquamative interstitial pneumonia/respiratory bronchiolitis ILD was in normal range, while the total count of macrophages was almost ten times higher than in normal BALF of nonsmoking subjects.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, it should be pointed that reporting cell proportions is, in fact, limited to showing relativity, and this may be misleading. A good example can be seen in our previous studies on sr-ILD [20]. The differential cell count in the BALF of patients with desquamative interstitial pneumonia/respiratory bronchiolitis ILD was in normal range, while the total count of macrophages was almost ten times higher than in normal BALF of nonsmoking subjects.…”
Section: Discussionmentioning
confidence: 78%
“…Cigarette smoking is also a risk factor for various lung diseases [19], [20], [21], [22] such as chronic obstructive pulmonary disease (COPD), usual interstitial pneumonia (UIP), desquamative interstitial pneumonia (DIP), respiratory bronchiolitis associated interstitial lung disease (RB-ILD) and pulmonary Langerhans cell histiocytosis (PLCH). Since these patients may undergo BAL as a part of a clinical investigation [19], [23], it is important to distinguish inflammatory changes due to cigarette smoking per se from changes due to the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since these patients may undergo BAL as a part of a clinical investigation [19], [23], it is important to distinguish inflammatory changes due to cigarette smoking per se from changes due to the disease. The establishment of a standardized reference material for BAL in asymptomatic smokers may contribute to a better interpretation and utility of this important diagnostic tool in a clinical framework.…”
Section: Introductionmentioning
confidence: 99%
“…A pronounced immunomodulatory effect of tobacco smoke has been proven: it affects not only the respiratory system but it also induces systemic alterations [8,9]. In our own studies we found a significant effect of tobacco smoking on lesions in pulmonary environment: in BALs obtained from smokers a proportion of helper Th lymphocytes (CD4 + ) was reduced and that of cytotoxic Tc lymphocytes (CD8 + ) was increased.…”
Section: Analysis Of Immune System Cells In Lung Carcinomamentioning
confidence: 52%